Clinical application of prion-like seeding in α-synucleinopathies: Early and non-invasive diagnosis and therapeutic development - Li, Jiaqi; Luo, Haiyang; Zheng, Honglin; Duan, Suying; Zhao, Taiqi; Yuan, Yanpeng; Liu, Yutao; Zhang, Xiaoyun; Wang, Yangyang; Yang, Jing; Xu, Yuming (Frontiers in Molecular Neuroscience, 2022)
The accumulation and deposition of misfolded α-synuclein (α-Syn) aggregates in the brain is the central event in the pathogenesis of α-synucleinopathies, including Parkinson’s disease, dementia with Lewy bodies, and multiple-system atrophy. To date, the diagnosis of these disorders mainly relies on the recognition of clinical symptoms in an advanced phase. Differential diagnosis among the various α-synucleinopathies subtypes remains challenging. Misfolded α-Syn can template its native counterpart into the same misfolded one within or between cells, behaving as a prion-like seeding. Protein-misfolding cyclic amplification and real-time quaking-induced conversion are ultrasensitive protein amplification assays initially used for the detection of prion diseases. These assays have shown high sensitivity and specificity in detecting α-synucleinopathies even at the pre-clinical stage recently. Herein, we collectively reviewed the prion-like properties of α-Syn and critically assessed the detection techniques of α-Syn-seeding activity. The progress of test tissues, which tend to be less invasive, is presented, particularly nasal swab, which is now widely known owing to the global fight against coronavirus disease 2019. We highlight the clinical application of α-Syn seeding in early and non-invasive diagnosis. Moreover, some effective therapeutic perspectives and clinical trials targeting α-Syn-seeding mechanisms are presented.